Glycyl‐l‐histidyl‐l‐lysine‐Cu2+ rescues cigarette smoking‐induced skeletal muscle dysfunction via a sirtuin 1‐dependent pathway - Mingming Deng; Qin Zhang; Liming Yan; Yiding Bian; Ruixia Li; Jinghan Gao; Yingxi Wang; Jinrui Miao; Jiaye Li; Xiaoming Zhou; Gang Hou (Wiley, 2023)
Abstract Background Skeletal muscle dysfunction is an important co‐morbidity in patients with chronic obstructive pulmonary disease (COPD) and is significantly associated with increased mortality. Oxidative stress has been demonstrated an important trigger for COPD‐related skeletal muscle dysfunction. Glycine‐histidine‐lysine (GHK) is an active tripeptide, which is a normal component of human plasma, saliva, and urine; promotes tissue regeneration; and acts as an anti‐inflammatory and antioxidant properties. The purpose of this study was to determine whether GHK is involved in COPD‐related skeletal muscle dysfunction. Methods The plasma GHK level in patients with COPD (n = 9) and age‐paired healthy subjects (n = 11) were detected using reversed‐phase high‐performance liquid chromatography. The complex GHK with Cu (GHK‐Cu) was used in in vitro (C2C12 myotubes) and in vivo experiments (cigarette smoking [CS]‐exposure mouse model) to explore the involvement of GHK in CS‐induced skeletal muscle dysfunction. Results Compared with healthy control, plasma GHK levels were decreased in patients with COPD (70.27 ± 38.87 ng/mL vs. 133.0 ± 54.54 ng/mL, P = 0.009). And plasma GHK levels in patients with COPD were associated with pectoralis muscle area (R = 0.684, P = 0.042), inflammatory factor TNF‐α (R = −0.696, P = 0.037), and antioxidative stress factor SOD2 (R = 0.721, P = 0.029). GHK‐Cu was found to rescue CSE‐induced skeletal muscle dysfunction in C2C12 myotubes, as evidenced by increased expression of myosin heavy chain, reduced expression of MuRF1 and atrogin‐1, elevated mitochondrial content, and enhanced resistance to oxidative stress. In CS‐induced muscle dysfunction C57BL/6 mice, GHK‐Cu treatment (0.2 and 2 mg/kg) reduces CS‐induced muscle mass loss (skeletal muscle weight (1.19 ± 0.09% vs. 1.29 ± 0.06%, 1.40 ± 0.05%; P < 0.05) and muscle cross‐sectional area elevated (1055 ± 552.4 μm2 vs. 1797 ± 620.9 μm2, 2252 ± 534.0 μm2; P < 0.001), and also rescues CS‐induced muscle weakness, indicated by improved grip strength (175.5 ± 36.15 g vs. 257.6 ± 37.98 g, 339.1 ± 72.22 g; P < 0.01). Mechanistically, GHK‐Cu directly binds and activates SIRT1(the binding energy was −6.1 kcal/mol). Through activating SIRT1 deacetylation, GHK‐Cu inhibits FoxO3a transcriptional activity to reduce protein degradation, deacetylates Nrf2 and contribute to its action of reducing oxidative stress by generation of anti‐oxidant enzymes, increases PGC‐1α expression to promote mitochondrial function. Finally, GHK‐Cu could protect mice against CS‐induced skeletal muscle dysfunction via SIRT1. Conclusions Plasma glycyl‐l‐histidyl‐l‐lysine level in patients with chronic obstructive pulmonary disease was significantly decreased and was significantly associated with skeletal muscle mass. Exogenous administration of glycyl‐l‐histidyl‐l‐lysine‐Cu2+ could protect against cigarette smoking‐induced skeletal muscle dysfunction via sirtuin 1.